INTEGRATION OF CORPORATE SOCIAL RESPONSIBILITY AND HUMAN RESOURCE MANAGEMENT IN SUPPORTING SUSTAINABLE DEVELOPMENT IN INDONESIAN SOES: A THEORETICAL REVIEW - Zulfikar Akbar; Nurita Andriani; Muh. Syarif (CV. Adiba Aisha Amira, 2026)
The integration of Corporate Social Responsibility (CSR) and Human Resource Management (HRM) has become increasingly crucial in supporting sustainable development, particularly in State-Owned Enterprises (SOEs/BUMN) in Indonesia. This theoretical review examines the synergy between CSR practices and HRM functions in achieving the Sustainable Development Goals (SDGs). Using a systematic literature review approach, this study analyzes the theoretical framework that connects CSR and HRM as strategic instruments for sustainable organizational performance. The findings indicate that the integration of Green Human Resource Management (GHRM) with CSR initiatives creates a multiplier effect in achieving economic, social, and environmental sustainability. SOEs in Indonesia face unique challenges and opportunities in implementing this integration due to their dual mandate as profit-oriented entities and agents of public welfare. This study contributes to the literature by proposing a conceptual framework for CSR-HRM integration specifically designed for the Indonesian SOE context, emphasizing the importance of stakeholder engagement, organizational culture, and regulatory compliance. The implications suggest that effective integration requires alignment between corporate strategy, HR policies, and sustainability objectives to maximize long-term value creation for all stakeholders.